Antibiogram, Plasmid Pattern, and Biofilm Formation in Clinical Isolates of P. aeruginosa (Journal of the College of Basic Education, 2022)
In this study eight hundred sample of (wound, burn, cystic fibrosis) were collected from patients admitted to Emergency hospital, Hawler teaching hospital, Pediatric hospital and private laboratory in Erbil during the period of February 2011 to September 2011. One hundred isolates of Pseudomonas aeruginosa were identified by using cultural, morphological characteristics, biochemical test and Api 20NE system in addition to vitek machine. Results of pigments production revealed the ability of P. aeruginosa to produce various pigments including blue / green, yellow/ green , and brown/ blue . The susceptibility of P. aeruginosa isolates to different antibiotics was examined. Impenim was the most effective antimicrobial agents against P. aerugionsa isolates and most of isolates showed high resistance degree to doxycycline 100%, Tetracycline 100%, Vancomycin 100%, Rifampcin 96%, Ampicillin 95%, Chloramphenicol 94%, Trimethoprim 83%, Amoxacillin 81%, Streptomycin 76%, Ceftriaxone 73%, Amikacin 67%, Cefotaxime 62%, Gentamycin 54%, and Ciprofloxacillin 40%. Due to the resistance of the isolates to these antibiotics they were classified into twenty five groups that showed the sensitivity variation in their resistance to these antibiotics. All P. aerugionsa isolates were screened for their ability to produce B- lactamase & Extended spectrum Beta lactamase out of 69 of P. aeruginosa isolates 69% were found to produce β-lactamase using rapid iodometric method , while 48% of the isolates were found to produce ESBL. The plasmid profile for nine P. aerugimosa isolates which showed the highest antibiotic resistance were conducted and the results revealed that all isolates except p6, and p8 contain one band with molecular weight more than 10kb using Agarose gel electrophoresis technique. The ability of P. aerugionsa to produce biofilm were studied , and the results showed that An among 97% of the isolates 71% were strongly biofilm producer, 20% were moderately biofilm producer, and 6% were weakly produce biofilm while 3% were non biofilm producer